A Questioning of the Thermal Sensation Vote Index Based on Questionnaire Survey for Real Working Environments. (January 2016) - Nastase, Ilinca; Croitoru, Cristiana; Lungu, Cătălin
Abstract: Throughout this paper, we present the results of the thermal comfort analysis in a real office using subjective data from questionnaires survey and experimental data from a thermal manikin prototype and a standardized measurement system was presented. The comparison between TSV of the questionnaires and the PMV of the Comfort Sense data showed a great dispersion for the TSV while the values of the PMV from the standardized system and from the thermal manikin were found to be close. The agreement between the thermal manikin data and the standardized system data should be related in our opinion to the possibility of having of a large scale distributed measurement system that reproduces both the global predicted thermal sensation of a real space but also gives the possibility of investigating local discomfort trough the local distributions of the equivalent temperature of the segments of the manikin. This kind of representation allows for instance the inspection of the uniformity of an environment.